O trabalho dos assistentes sociais no âmbito hospitalar: as particularidades da sua inserção no Hospital Universitário Onofre Lopes (HUOL), em Natal/RN - Nascimento, Monica Matias Rafael do (2011)
This study aimed to analyze the work of social workers at the Hospital Universitário Onofre Lopes (HUOL), with the analytical approach the contracting process with the HUOL with the National Health System (SUS), which is set from 2004. Thus, this study sought in times of state reform, restructuring and tension between enlargement / reduction of social and labor rights, understanding the limits and possibilities of social work in HUOL, analyzing how these determinations bounce in the practice of social workers included in the collective process of health work. From a theoretical and methodological historical and dialectical materialism, we conducted literature search, in which developed book report and readings of texts, articles, books that focus on the central categories of the study, namely: Work, Social Work, Health, Health Reform , Project ethical and professional politician. Operationalized also a documentary research, on the Brazilian Public Health Policy, (SUS) and of the Education, as well as research field in which we conducted interviews with 11 social workers, employees packed the HUOL. We conclude that social workers did not participate in the discussion process of contracting the HUOL with the Municipal Health Secretariat of Natal, RN, manager of health and full resetting of user access, via reference setting - counter-referral services provided by the hospital brought the main demands on Social Work guidance regarding the functionality of SUS, and the social intervention in the struggle to guarantee such access. However, the data show that the expansion of demands that require the intervention of the social worker at HUOL is not associated with quantitative growth of these professionals need. Such conditions inflect the possibilities of materialization of the professional ethical-political project, even though that these professionals worry and seek the intellectual improvement, quality of service and to guarantee the social rights of users in the professional practice everyday